Apakah Inflasi, Pendapatan Pajak Daerah, dan Pengeluaran Pemerintah Mempengaruhi Pertumbuhan Ekonomi? Analisis Makroekonomi di Pulau Jawa - April Kurniawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The growth of Gross Regional Domestic Product (GRDP) as a benchmark for a region's economic growth is closely linked to regional tax revenue and government expenditure, as these policies are components of aggregate demand, whose increase will drive GRDP growth. On the other hand, inflation is an economic phenomenon that is always intriguing to discuss, particularly regarding its broad impact on economic growth. This study aims to analyze the impact of inflation, regional tax revenue, and government expenditure on economic growth across provinces in Java Island from 2010 to 2019. The data analysis method used is Vector Autoregression (VAR) analysis, employing EViews 10 software. The study's findings indicate that inflation has a significant positive effect on economic growth. Meanwhile, regional tax revenue and government expenditure have a positive but not significant impact on economic growth. As a fiscal policymaker, the government must be cautious in managing the state revenue and expenditure budget, ensuring that sectors prone to price increases in goods and services are carefully monitored. Additionally, the government should continue to optimize regional tax collection while maintaining efficient spending to increase government savings, which are essential for development, particularly in opening economic sectors in underdeveloped areas.